PANDANGAN ASGHAR ALI ENGINEER TENTANG KESETARAAN GENDER - Rosnaeni Rosnaeni (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2021)
AbstrakThis research is to find out Asghar Ali Engineer's view on gender equality. The type of research used in the article is a literature review. The data used in this study are document data, both from textbooks, scientific journals, and other relevant document sources. The results of the study indicate that gender equality is an equal condition for men and women to obtain opportunities and their rights as human beings, in order to be able to play a role and participate in political, legal, economic, socio-cultural, educational, defense and national security activities as well as equality in enjoy the results of this development. In Islam there is a figure who discusses gender equality, namely Asghar Ali Engineer. She is an Islamic feminist figure from India. According to Asghar Ali Engineer, the basic view of Ali Ashgar about gender equality is that it has two normative and contextual aspects. According to Asghar Ali Engineer, Islam places women in the same position as men. This similarity can be seen from three things, namely: first, from the nature of humanity. second, Islam teaches that both women and men get the same reward for the good deeds they do. Third, Islam does not tolerate unfair treatment and differences between human beings.Keywords: Asghar Ali Engineer's View, Gender Equality